Exploring Flexible and Low-Cost Alternatives to Face-to-Face Academic Support - Dobozy, Eva; Martin, Romana (IATEFL, 2009)
In this paper we address some of the issues surrounding the use of educational technology solutions with first year net generation students in an introductory education studies unit. These issues include the need for more engaging learning experiences, the role of technology in supporting this need, and the possible mismatch between expectations and actual needs. The student usage and access of a low-cost, flexible alternative to face-to-face individual or group-based academic support was the focus of this case study. We describe our rationale and attempt to help students with their assignment requirements in a first year teacher education unit through the development of a small-scale self-directed intervention program, and report on student engagement with the model. Analysis of the data brings to light findings that have implications for policy design and shows a need for timely research to better inform lecturers of their students’ digital literacy, acceptance and access, and use of innovative learning designs. This also highlights the requirement for a greater awareness of the technologies that students embrace, the technologies that may pose a challenge and the differing needs of first year students to those of the more experienced learners.